Laparoendoscopic single-site myomectomy using conventional laparoscopic instruments and glove port technique: Four years experience in 109 cases - Szu-Yu Chen; Bor-Ching Sheu; Su-Cheng Huang; Wen-Chun Chang (Taiwanese Journal of Obstetrics & Gynecology, 2017)
Objective: To report a single surgeon's experience with 109 laparoendoscopic single-site myomectomy (LESS-M) using conventional laparoscopic instruments and a homemade glove port system. Materials and methods: A total of 109 consecutive women who underwent LESS-M between March 2011 and April 2015 were reviewed. Results: The mean age and body mass index were 38.3 ± 6.5 years and 22.1 ± 3.0 kg/m2. The mean diameter of the largest myoma and the mean number of myomas were 8.1 ± 2.4 cm and 1.6 ± 0.7. The mean weight of the myomas was 223.2 ± 159.7 g. The most common type of myoma was intramural (61%), followed by subserosal (23%), submucosal (9%), and intraligamental (7%). The most common site of the myomas was anterior (39%), followed by posterior (38%), lateral (15%), and fundal (9%). The mean operative time and estimated blood loss were 138.5 ± 43.8 min and 104.9 ± 270.1 mL. Two patients (1.8%) required intraoperative transfusion. The mean hospital stay was 2.5 ± 0.6days. There were no conversions to laparotomy, but three patients(2.8%) were converted to two-port laparoscopic myomectomy. No patient experienced any major complication, including bowel, ureter, bladder injuries, or incisional hernia. Six women became pregnant after the operation, and five of these patients delivered their babies at full term by cesarean section. One patient delivered her baby at a gestational age at 32 weeks due to idiopathic polyhydramnios by cesarean section. One patient had the second pregnancy and delivery after LESS-M. Fourteen patients (12.8%) had small recurrent myomas that did not require treatment. Conclusion: LESS-M is a feasible alternative for patients with symptomatic myomas, and this technique can provide cosmetic advantages compared to conventional laparoscopic surgery.